The Single Wire Ureteral Access Sheath, Both Safe and Economical - Joan C. Delto; George Wayne; Ajaydeep Sidhu; Rafael Yanes; Akshay Bhandari; Alan M. Nieder (Advances in Urology)
Introduction. Novel disposable products for ureteroscopy are often inherently more expensive than conventional ones. For example, the Cook Flexor© Parallel™ (Flexor) access sheath is designed for ease and efficiency of gaining upper tract access with a solitary wire. We analyze the cost combinations, efficiency, and safety of disposable products utilized for upper tract access, including the Flexor and standard ureteral access sheath. Methods. We performed a retrospective review from January 2014 to October 2014 of patients undergoing URS for nephrolithiasis, who were prestented for various reasons (e.g., infection). Common combinations most utilized at our institution include “Classic,” “Flexor,” and “Standard.” Total costs per technique were calculated. Patient characteristics, operative parameters, and outcomes were compared among the groups. Results. The most commonly used technique involved a standard ureteral sheath and was the most expensive ($294). The second most utilized and least expensive combination involved the Flexor, saving up to $80 per case (27%). All access sheaths were placed successfully and without complications. There were no significant differences in operative time, blood loss, or complications. Conclusions. In prestented patients within this study, the Flexor combination was the most economical. Although the savings appear modest, long-term impact on costs can be substantial.